Enhanced optical and photocatalytic properties of Ag NPs decorated-ZnO composites - Burachat Dangsaart; Kanokthip Boonyarattanakalin; Chatpong Bangbai; Apichart Apichart; Krisana Chongsri (Thai Journal of Nanoscience and Nanotechnology, 2024)
The goal of this work is to synthesize and study composites of silver and zinc oxide nanoparticles for improved ZnO light absorption by the aggregation of Ag nanoparticles prepared by a simple process. Starting with the synthesis of silver nanoparticles from silver nitrate (Silver Nitrate; AgNO3 ), the concentration of the synthesis of silver nanoparticles and zinc oxide composites was changed to 0.2%, 0.6%, and 1.0%. Initially, the amount of silver nanoparticles of 0.2%, 0.6%, and 1.0 % per 3 g of zinc oxide was carried out to determine the amount of silver nanoparticles suitable for important properties. Morphological analysis was performed using scanning electron microscopy (SEM). The crystal structure was analyzed by X-ray diffraction. The study on absorbance using the diffuse reflectance UVvisible spectroscopy technique and the photocatalytic efficiency was assessed by the decomposition of organic dyes under visible light. The analysis revealed that the silver nanoparticles and zinc oxide composites were morphologically cuboid and rod-shaped. As for the crystal structure, it was found to be hexagonal. The absorbance of composite materials is lower than that of pure zinc oxide in the 405600 nm range. Silver nanoparticles will enhance light absorption in composite materials due to their favorable surface plasmon resonance characteristics. This enhances composite materials' optical absorption. The breakdown of organic dyes under visible light was used to measure the photocatalytic efficiency, and it was discovered that the best photocatalytic properties were obtained with Ag NPs 0.2% per 3 g of ZnO.
Keywords: Advanced Photocatalysis Techniques